Plate D: Powder magazine; powder instruments; rocket molds - Siemienowicz, Kazimierz (Artis Magnae Artilleriae, 1650)
Fig. 17: Plan of a powder magazine by Eugenio Gentilini. Fig. 18: A new instrument for measuring gunpowder. Fig. 19: Sieve. Figs. 20 and 21: Rocket molds.
Keywords: Rocketry; Military architecture--Designs and plans; Artillery